2011
DOI: 10.1103/physrevc.84.054006
|View full text |Cite
|
Sign up to set email alerts
|

Dynamical coupled-channels study ofK*K*¯andωφstates in a chiral quark model

Abstract: A dynamical coupled-channel study of K * K * state with isospin 0 and ωφ state is performed within both the chiral SU(3) quark model and the extended chiral SU(3) quark model by solving a resonating group method (RGM) equation. The model parameters are taken from our previous work, which gave a satisfactory description of the energies of the octet and decuplet baryon ground states, the binding energy of the deuteron, the nucleon-nucleon (N N ) scattering phase shifts, and the hyperon-nucleon (Y N ) cross secti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2012
2012
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…In this work, we will study the two resonances based on our chiral quark model. It should be stressed that the chiral quark model is successful to describe well the binding energies of the baryon ground states, the binding energy of the deuteron, the NN scattering phase shifts and the NY cross sections simultaneously [17][18][19][20][21][22][23][24][25][26]. It is expected that the chiral quark model provides another way to study the possible B B * and B * B * bound states problem on a quark level.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In this work, we will study the two resonances based on our chiral quark model. It should be stressed that the chiral quark model is successful to describe well the binding energies of the baryon ground states, the binding energy of the deuteron, the NN scattering phase shifts and the NY cross sections simultaneously [17][18][19][20][21][22][23][24][25][26]. It is expected that the chiral quark model provides another way to study the possible B B * and B * B * bound states problem on a quark level.…”
Section: Introductionmentioning
confidence: 99%
“…It should be mentioned that several works based on our chiral quark model have been published [17][18][19] to study the bound states and binding energies of heavy-meson molecular systems with the resonating group method (RGM). The RGM method is a successful one proficiently adopted in [17][18][19][20][21][22][23][24][25][26]. In this work, different from the RGM method, we apply the approach introduced in [42] to derive the analytical form of the total effective interaction potentials between the two S-wave heavy mesons.…”
Section: Introductionmentioning
confidence: 99%
“…decays, so they are lower bounds to the total width. Overall, a narrow glueball with ΓG ∼ 0.2 GeV seems a plausible theory prediction (I do not list the additional 1.81 GeV structure in ωφ since later analysis confirmed that a new resonance should also be manifest in KK, which it is not, and that it likely is the same f0(1710) seen at a higher mass due to the ωφ threshold distortion [27,28] to work better (but yield broader glueballs) the higher the mass M G , because (a) the coupling constant α s becomes smaller with increasing gluon momentum so that perturbation theory is sounder, and (b) there are more abundant intermediate hybrid mesons in the high spectrum, so some will always be near the energy-shell M G in the decay. This was estimated for the scalar glueball at M G 1.8 GeV [30] and found to yield a relatively narrow state with Γ G 0.1 GeV, with a larger ππ than KK component as demanded by phase space, as shown in table 1.…”
Section: Coupling To Quarks and Glueball Widthmentioning
confidence: 99%